Educational And Support Group Interventions To Improve Adherence In Hypertensive Patients: A Systematic Review - Kartika Milaningrum; Makhfudli Makhfudli; Eka Mishbahatul M. Has (Jurnal Ners, 2026)
Hypertension is a chronic condition frequently associated with poor treatment adherence, emphasizing the importance of self-care–based intervention strategies. This systematic review aims to assess the effectiveness of educational and support group interventions rooted in self-care theory in enhancing adherence and controlling blood pressure among individuals with hypertension. The review followed the PRISMA 2020 guidelines, with articles retrieved from seven databases (Scopus, PubMed, ProQuest, ScienceDirect, SAGE Journals, Springer Nature, and Cochrane Library) published between January 2020 and December 2025. Eligible studies were randomized controlled trials (RCTs) that evaluated the impact of education or support interventions on adherence and blood pressure outcomes. Methodological quality was assessed using the JBI Critical Appraisal Checklist. Out of 320 identified articles, 9 RCTs met the inclusion criteria, conducted in Indonesia, Iran, Egypt, China, and Turkey, involving a total of 1,011 participants aged 60–74 years. The interventions included structured education sessions, self-directed modules based on self-care theory, group discussions, and peer support activities. Most studies reported improvements in medication adherence and healthy lifestyle behaviors, along with significant reductions in both systolic and diastolic blood pressure. Self-care–based interventions were found effective in increasing patient engagement in hypertension management. However, the diversity in intervention formats and durations highlights the need for standardization. These strategies are feasible for implementation in both community and primary care settings.